2011
DOI: 10.1093/infdis/jir621
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Biological Functions of Tryptophan Catabolizing Enzymes During Intracellular Infection

Abstract: Recent studies have underscored physiological and pathophysiological roles for the tryptophan-degrading enzyme indolamine 2,3-dioxygenase (IDO) in immune counterregulation. However, IDO was first recognized as an antimicrobial effector, restricting tryptophan availability to Toxoplasma gondii and other pathogens in vitro. The biological relevance of these findings came under question when infectious phenotypes were not forthcoming in IDO-deficient mice. The recent discovery of an IDO homolog, IDO-2, suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
103
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 52 publications
4
103
0
Order By: Relevance
“…In vivo blocking of IDO increases the burden of parasites such as T. gondii (18) and Trypanosoma cruzi (41) and of fungi (Candida albicans (42)) in mice, which seems consistent with its antimicrobial role in vitro. In contrast, inhibition or deficiency of enzyme during other parasitic (Leishmania donovani (18) and Trichuris muris (43)) and bacterial (Citrobacter rodentium (44)) infections reduced the pathogen burden in animals.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In vivo blocking of IDO increases the burden of parasites such as T. gondii (18) and Trypanosoma cruzi (41) and of fungi (Candida albicans (42)) in mice, which seems consistent with its antimicrobial role in vitro. In contrast, inhibition or deficiency of enzyme during other parasitic (Leishmania donovani (18) and Trichuris muris (43)) and bacterial (Citrobacter rodentium (44)) infections reduced the pathogen burden in animals.…”
Section: Discussionmentioning
confidence: 52%
“…In contrast, inhibition or deficiency of enzyme during other parasitic (Leishmania donovani (18) and Trichuris muris (43)) and bacterial (Citrobacter rodentium (44)) infections reduced the pathogen burden in animals. Moreover, 1-MT, a competitive inhibitor of IDO, had none (herpes simplex virus 1) to a negative (BM5) influence on the virus replication in mice (18,45), which occasionally differs with in vitro findings (46). Likewise, IDO1 as a positive determinant of Eimeria growth does not reconcile with canonical antimicrobial function, notwithstanding a potential depletion of tryptophan in the infected host cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, IDOtryptophan-directed immunosuppression is thought to play a role in infections by Leishmania major (90), human immunodeficiency virus (reviewed in reference 91), hepatitis C virus (92,93), human papillomavirus (94), Listeria monocytogenes (95), Mycobacterium tuberculosis (96), Candida albicans (97), and Aspergillus fumigatus (98). Importantly, a recent study investigating the role IDO plays in infections by two protozoal species, T. gondii and L. major, found that IDO facilitates T. gondii clearance and suppresses L. major clearance, highlighting the opposing and pathogen-specific roles that IDO can have in infectious disease (90).…”
Section: Pathogen Defence Via Ido (Indoleamine 23-dioxygenase)-mediamentioning
confidence: 99%
“…When the therapeutic inhibition of IDO-1 is considered, it is important to mention that IDO-1 can have contradictory functions: it can exert immunoregulatory (Leishmania major) and antimicrobial (Toxoplasma gondii, Trypanosoma cruzi) effects, which are specific for the individual pathogen (31), with the molecular mechanisms being largely unknown. The most frequently used IDO inhibitor is 1-methyl-D-tryptophan (1-MDT), which has reached phase 1 clinical trials as an adjunct to conventional chemotherapy of cancer, since many tumors express IDO for immune suppression (15).…”
mentioning
confidence: 99%